Formulation of Facial Wash from Nettle Leaf (Urtica Dioica L.) Ethanol Extract - Mutiara Agustina Nasution; Zuhairiah Nasution; Fitria Mahdani (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
Face wash is a facial cleanser in the form of a gel containing foam which is recommended for sensitive, oily and acne prone skin. One of the natural ingredients that can be developed is nettle (Urtica dioica L.). The aim of this study was to to determine the potential of nettle leaf extract facial wash. The process of making nettle leaf extract using the maceration method with ethanol as a solvent. The results of the characteristics of nettle leaf simplicia powder obtained 13.78% water content, 37.7% water soluble extract content, 37.89% ethanol soluble extract content, 14.69% total ash content. The screening of simplicia powder results were positive for containing alkaloids, flavonoids, terpenoids, steroids, saponins, tannins. From the research that has been done, it can be concluded that ethanol extract of nettle leaves can be formulated in a facial wash with a variation of concentration of 5%, 10% and 15%.